Diversity of invited speakers at endocrinology conferences. (16th December 2021) - Gamage, Isuru; Bolland, Mark J.; Sadler, Lynn; Dalbeth, Nicola; Grey, Andrew
Abstract: Objective: To assess diversity of gender and geographical location of institutional affiliation among invited speakers at major international endocrinology conferences. Design and Methods: Descriptive study of characteristics of invited speakers at eight general and discipline‐specific endocrinology conferences held annually in Europe and North America 2013–2019. Main outcomes were gender, geographical location of institutional affiliation and frequency of repeat presentations among invited speakers. Results: Of 2375 invited speakers who gave 3522 presentations, 843 (35.5%) were women. Five hundred and ninety‐four (25.0%) speakers gave >1 presentation at any conference. The proportion of women speakers declined as the number of presentations per speaker increased. Of speakers giving two and seven presentations, respectively, 36.0% and 20.0% were women. 52.9% of speakers were from institutions in North America, and 25.6% from institutions in Western Europe. Fewer than 5% of speakers were from institutions in each of Eastern Europe, Asia, South America, Africa and Oceania. The proportions of speakers who were women and from each geographical area were unchanged over 7 years. Up to one in three speakers gave >1 presentation at an individual conference (range 9.9%–32.2%). Conclusions: Women and speakers from institutions outside of North America and Western Europe are underrepresented among invited speakers at major international endocrinology conferences. Longitudinal data indicate no change in either speaker characteristic over the time period examined. These underrepresentations are more marked among speakers who give repeat presentations.